Kombinasi Breast Care dan Acupressure Points for Lactation untuk Meningkatkan Kecukupan Air Susu Ibu (ASI) bagi Bayi - Nana Usnawati; Astin Nur Hanifah; Triana Septianti Purwanto (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Acupressure points for lactation is to provide acupressure on specific meridian points in the breast area for optimization of prolactin and oxytocin receptors. The purpose of this study was to analyze the effectiveness of the combination method of "Breast care" and "Acupressure points for lactation" on the adequacy of breast milk for infants. This study applied a one group post test design. The sample in this study were all post partum mothers and their babies at PMB Ny. “W”, RB Bunda Panekan, PMB Sr. Jabung and PMB Snt Selotinatah, Magetan from May to August 2020. The sample size was 30, which was taken by consecutive sampling. Data were collected through interviews about the adequacy of breast milk for infants, then analyzed descriptively. Based on the criteria for the adequacy of breast milk, most of the respondents met the 10 criteria for adequacy, which were included in the sufficient category. Furthermore, it was concluded that the combination of "breast care" and "accupressure point for lactation" was effective in increasing the adequacy of breast milk for infants.Keywords: breast care; accupressure points for lactation; combination; sufficient breast milk; baby ABSTRAK Acupressure points for lactation adalah memberikan akupresur pada titik-titik meridian khusus di daerah payudara untuk optimalisasi reseptor prolaktin dan oksitosin. Tujuan penelitian adalah menganalisis efektifitas metode kombinasi “Breast care” dan “Acupressure points for lactation” terhadap kecukupan ASI bagi bayi. Penelitian ini menerapkan one group post test design. Sampel dalam penelitian ini adalah seluruh ibu post partum dan bayinya di PMB Ny. “W”, RB Bunda Panekan, PMB Sr. Jabung dan PMB Snt Selotinatah, Magetan pada bulan Mei sampai Agustus 2020. Besar sampel adalah 30, yang diambil secara consecutive sampling. Data dikumpulkan melalui wawancara  tentang kecukupan air susu ibu bagi bayi, selanjutnya dianalisis secara deskriptif. Berdasarkan kriteria kecukupan air susu ibu, sebagian besar responden memenuhi 10 kriteria kecukupan, yakni termasuk dalam kategori cukup. Selanjutnya disimpulkan bahwa kombinasi “Breast care” dan “Accupressure point for lactation” efektif untuk meningkatkan kecukupan air susu ibu bagi bayi.Kata kunci: breast care; accupressure point for lactation; kombinasi; kecukupan air susu ibu; bayi